2009
DOI: 10.1152/ajplung.00293.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide improves lung structure and pulmonary hypertension in a model of bleomycin-induced bronchopulmonary dysplasia in neonatal rats

Abstract: Tourneux P, Markham N, Seedorf G, Balasubramaniam V, Abman SH. Inhaled nitric oxide improves lung structure and pulmonary hypertension in a model of bleomycin-induced bronchopulmonary dysplasia in neonatal rats. Am J Physiol Lung Cell Mol Physiol 297: L1103-L1111, 2009. First published October 16, 2009 doi:10.1152/ajplung.00293.2009.-Whether inhaled nitric oxide (iNO) prevents the development of bronchopulmonary dysplasia (BPD) in premature infants is controversial. In adult rats, bleomycin (Bleo) induces lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 61 publications
4
43
1
1
Order By: Relevance
“…In neonatal rats, our laboratory and others have reported that repeated systemic administration of bleomycin leads to a selective decrease in lung growth, along with arrested alveolarization, vascular hypoplasia, and chronic PHT (15,30,44,52), similar to the lung pathology observed in human infants with severe BPD. We have employed this model to demonstrate a critical role for macrophage influx and macrophagederived tumor necrosis factor (TNF)-␣ in the pathogenesis of chronic PHT (26,44).…”
mentioning
confidence: 54%
“…In neonatal rats, our laboratory and others have reported that repeated systemic administration of bleomycin leads to a selective decrease in lung growth, along with arrested alveolarization, vascular hypoplasia, and chronic PHT (15,30,44,52), similar to the lung pathology observed in human infants with severe BPD. We have employed this model to demonstrate a critical role for macrophage influx and macrophagederived tumor necrosis factor (TNF)-␣ in the pathogenesis of chronic PHT (26,44).…”
mentioning
confidence: 54%
“…Previous studies from our group have established a model of repeated systemic bleomycin injection in neonatal rats that results in lung injury mimicking characteristics typical of BPD. This model is a useful tool to help understand mechanisms contributing to lung development and remodeling (31) but also to study the effects of therapeutic interventions aimed at preventing lung parenchymal and vascular injury (31,50,56).The chemotherapeutic agent bleomycin sulfate causes a pulmonary inflammatory and fibrotic response in rodents when instilled as a single intratracheal dose (27) or by repeated intraperitoneal injection (3). Bleomycin-induced lung injury is characterized by induction of proinflammatory cytokines (18), influx of macrophages and other inflammatory cells (23), "emphysematous" lung morphology, and severe PHT (49, 60).…”
mentioning
confidence: 99%
“…Previous studies from our group have established a model of repeated systemic bleomycin injection in neonatal rats that results in lung injury mimicking characteristics typical of BPD. This model is a useful tool to help understand mechanisms contributing to lung development and remodeling (31) but also to study the effects of therapeutic interventions aimed at preventing lung parenchymal and vascular injury (31,50,56).…”
mentioning
confidence: 99%
“…Bleomycin has been suggested as the main factor in causing pulmonary veno-occlusive disease in a reported series of patients [63,64]. Bleomycin has long track of being used in experimental studies to induce idiopathic pulmonary fibrosis and pulmonary hypertension [65][66][67][68]. Management usually directed toward supportive treatment, steroids and azathioprine with a possible role for imatinib and bosentan [69][70][71].…”
Section: Bleomycinmentioning
confidence: 99%